(untitled) (Research, Society and Development, 2017)
Micro and small enterprises play a key role in the Brazilian economy and, to survive in a highly globalized market, where fierce competition may involve risks and uncertainties, the use of tools that optimize the decision-making process is needed, which directly influences the performance of company. Thus, the main objective of this work is to analyze how the control indicators can contribute to making safer decisions in a small pharmaceutical company. We conducted a descriptive research with a qualitative approach. The data were collected through documentary research and semi-structured interviews with the main manager of the company. It was found the need and importance of using control indicators, as they demonstrate the real situation of the company, providing secure and important information that are nowadays unknown bycompany to reduce uncertainty in decision-making and contribute to increased efficiency, competitiveness and improved results.